Leadership: A Crucial Ingredient in Unstable Times - Catherine McDonald; Lesley Chenoweth (Social Work and Society)
Social work is experiencing an unprecedented degree of institutional instability, particularly in the advanced industrial nations which, to varying degrees and via differing paths, have abandoned the Keynesian Welfare State. It has been replaced with a fundamentally different workfare regime in which operates on quite different assumptions - all of which pose fundamental challenges to social work. The degree of change is such that it can be understood as institutional change. The profession needs a number of strategies in response the contemporary de-stabilization. Drawing on theoretical and empirical literature about institutional change we show why it is that professional leadership is crucial in the current environment. The paper reviews what in currently know about leadership, both in general and in relation to social work. Referring to the notion of institutional entrepreneurs and on the role played by other non-social work professional associations in situations of change, we articulate what role leadership can play. We conclude with recommendations about how leadership could be promoted, particularly by the professional associations.